2012
DOI: 10.1080/00063657.2012.684550
|View full text |Cite
|
Sign up to set email alerts
|

Coating plasticine eggs can eliminate the overestimation of predation on artificial ground nests

Abstract: Capsule The use of plasticine eggs coated with a thin layer of rubber instead of entirely plasticine eggs in dummy nests reduced the unnaturally high nest predation rate caused by attracted small mammals, while also enabling the identification of nest predators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…A body of research has used placement of nests of artificial bird eggs to explore the influence of habitat on egg predation. Studies with false nests to explore predation on bird eggs have usually relied on using a combination of real eggs (usually quail or finch eggs) and plasticine eggs (sometimes rubber coated to reduce olfactory cues, Purger et al ., ) to both induce and record predation events. Vetter, Rücker & Storch () carried out a meta‐analysis of edge effects on nest predation in tropical forests, using studies that made use of over 9000 artificial nests and eggs and found support for more predation along forest edges.…”
Section: The Questionssupporting
confidence: 83%
See 2 more Smart Citations
“…A body of research has used placement of nests of artificial bird eggs to explore the influence of habitat on egg predation. Studies with false nests to explore predation on bird eggs have usually relied on using a combination of real eggs (usually quail or finch eggs) and plasticine eggs (sometimes rubber coated to reduce olfactory cues, Purger et al ., ) to both induce and record predation events. Vetter, Rücker & Storch () carried out a meta‐analysis of edge effects on nest predation in tropical forests, using studies that made use of over 9000 artificial nests and eggs and found support for more predation along forest edges.…”
Section: The Questionssupporting
confidence: 83%
“…Purger et al . () recommend coating clay eggs with a thin layer of rubber to mitigate high scent cues and to reduce the unnaturally high nest predation recorded from artificial nests with plasticine eggs (e.g. Maier & Degraaf, ; Purger et al ., ).…”
Section: Interpretation and Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasticine eggs were made by hand to have the dimensions of a reference quail egg (3.5cm long, 2.8cm diameter), and were aerated for 3 days after manufacture to mitigate the strong scent. To reduce the scent further, plasticine eggs were coated with a thin layer of rubber (PlastiDip ® ) before aeration, which has been shown to reduce overestimation of mammalian predation rates (Purger et al, 2012). Eggs were marked on their base to identify the nest they were placed in, to assists in cases where an egg was removed from the nest but able to be recovered.…”
Section: Methodsmentioning
confidence: 99%
“…In each artificial nest, we placed one quail egg and one natural coloured plasticine egg of the same size. This imitation eggs were coated with PlastiDip® and had been aired for at least two weeks before the study began (Purger et al, 2012). The nests were then checked on days 1 (21 V), 3 (23 V), 6 (26 V), 10 (30 V) and 15 (4 VI) between 9:00 h and 14:00 h. During nest checking, which lasted no longer than 5 minutes, we recorded the number of cats, and free and leashed dogs observed around the nest to take into consideration the possibility that freely moving domestic animals found and destroyed the eggs in the artificial nests.…”
Section: Methodsmentioning
confidence: 99%